The miracle equation : the two decisions that move your biggest goals from possible, to probabe, to inevitable - Elrod, Hal, 1979- (Harmony Books, 2019)
Provides a plan to establish and maintain unwavering faith and put forth extraordinary effort in order to achieve positive outcomes.